VD_FINDINFO Jug / 2021 / 409 vom 19. Februar 2021 - VD Tribunal cantonal (2021)
GESTION DÉLOYALE, FAUX INTELLECTUEL DANS LES TITRES, COMPTABILITÉ, SURENDETTEMENT, ACQUITTEMENT | 725 CO, 158 ch. 1 al. 1 CP, 251 ch. 1 CP